An observational study of antibody responses to a primary or subsequent pertussis booster vaccination in Australian healthcare workers. Issue 11 (12th March 2021) - McAlister, Sonia M.; van den Biggelaar, Anita H.J.; Woodman, Tabitha L.; Hutton, Heidi; Thornton, Ruth B.; Richmond, Peter C.
Highlights: Primary and subsequent adult Tdap vaccinations are comparably immunogenic. Antibodies wane similarly in first and repeated Tdap-vaccinated whole cell primed adults. Immune memory is maintained up to 12 years after a first Tdap dose. Tetanus and diphtheria antibodies persist in adults not vaccinated since childhood. Repeated adult pertussis vaccination is important to maintain protection. Tetanus and diphtheria boosters may not need to be repeated frequently. Abstract: Adult pertussis vaccination is increasingly recommended to control pertussis in the community. However, there is little data on the duration and kinetics of immunity to pertussis boosters in adults. We compared IgG responses to vaccination with a tetanus, low-dose diphtheria, low-dose acellular pertussis (Tdap) booster at 1 week, 1 month and 1 year post-vaccination in whole-cell (wP)-primed Australian paediatric healthcare workers who had received an adult Tdap booster 5–12 years previously, to those who received their first Tdap booster. Tdap vaccination was well tolerated in both groups. Previously boosted adults had significantly higher pre-vaccination IgG concentrations for all vaccine-antigens, and more were seropositive for pertussis toxin (PT)-specific IgG (≥ 5 IU/mL) (69.5%; 95% confidence interval (CI) 59.5–79.5) than adults in the naïve group (45.2%; 95% CI 32.8-57.5). Tdap vaccination significantly increased IgG responses 1 month post-vaccination in both groups. This increase was more rapid in previously boosted than in naïve adults, with geometric mean fold-increases in PT-IgG at 1 week post vaccination of 3.6 (95% CI 2.9–4.3) and 2.6 (95% CI 2.2–3.2), respectively. Antibody waning between 1 month and 1 year post-vaccination was similar between groups for IgG specific to PT and filamentous haemagglutinin (FHA), but was faster for IgG against pertactin (PRN) in the naïve group (GMC ratio 0.36; 95% CI 0.31–0.42) than the previously boosted group (GMC ratio 0.45; 95% CI 0.39–0.50). At baseline, all but one adult had protective IgG titres against tetanus toxin (TT) (≥ 0.1 IU/mL), and 75.6% in the previously boosted and 61.3% in the naïve group had protective IgG titres against diphtheria toxoid (DT) of ≥ 0.1 IU/mL. This study shows that pertussis immune memory is maintained up to 12 years after Tdap vaccination in wP-primed Australian adults. There was no evidence that pertussis immune responses waned faster after a booster dose. These findings support current recommendations of repeating Tdap booster vaccination in paediatric healthcare workers at least every 10 years. Clinical trials registry: ACTRN12615001262594.